2022
DOI: 10.1088/1755-1315/1078/1/012052
|View full text |Cite
|
Sign up to set email alerts
|

Net zero emission buildings: next generation of benchmarks and calculation rules

Abstract: The definition of ambitious life cycle-based benchmarks and target values to limit the GHG emissions of buildings is seen as one of the most important steps in pushing the construction and real estate sector in significantly reducing its contribution to global warming. Especially target values are no longer only developed from a bottom-up perspective. There is now an interest by governments and sustainability assessment system providers in supplementing bottom-up approaches with science-based top-down approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Bottom-up approaches are based, for example, on statistical evaluations of building samples or on analyses of building archetypes [33].…”
Section: Benchmarking For Buildings' Greenhouse Gas Emissionsmentioning
confidence: 99%
“…Bottom-up approaches are based, for example, on statistical evaluations of building samples or on analyses of building archetypes [33].…”
Section: Benchmarking For Buildings' Greenhouse Gas Emissionsmentioning
confidence: 99%
“…To meet national and international climate goals, various GHG emission criteria and benchmark values for buildings are being developed [3]. However, there is a distinct lack of harmonisation in methods and approaches making it difficult to compare construction projects or implement and apply benchmarking at a national or international level [4,5]. Norway is no exception.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have compared environmental sustainability assessment schemes for buildings, whereby GHG emissions is often identified as an important criteria [15][16][17][18][19][20][21]. More recently, the IEA EBC Annex 72 has investigated net zero emission buildings and the next generation of benchmark and calculation rules and found that there are large differences in GHG emission targets for buildings [4]. Another study has investigated indicative baseline and decarbonisation pathways for embodied life cycle GHG emissions of buildings across Europe and found that whole life cycle (WLC) embodied carbon emissions range from 400 -800 kgCO 2 e/m 2 (6.6 -13.3 kgCO 2 e/m 2 /yr), averaging at 550 kgCO 2 e/m 2 (9.2 kgCO 2 e/m 2 /yr) for residential buildings [5].…”
Section: Introductionmentioning
confidence: 99%